Factor Affecting Profit Distribution Management In Islamic Commercial Banks: Moderation Of Return On Assets - Ernayani, Rihfenti (LPPM ISNJ Bengkalis, 2024)
This study aims to find empirical evidence of the influence of capital adequacy ratio (CAR), non-performing financing (NPF), and third-party financing (TPF) on profit distribution management, moderated by return on assets (ROA). This study employs a quantitative approach using panel data regression. The data is generated in numerical form using secondary data from financial reports obtained through the official website of the Indonesia Stock Exchanges (IDX). The Islamic commercial banks in Indonesia listed on the IDX 2016-2022 comprise the study population, and a purposive sampling method is used to determine the sample size so that a sample of 9 Islamic commercial banks with 63 observation data is obtained. EViews 10 is used for the data analysis method, and the random effect model (REM) is used for the research model. The research findings suggest that CAR, TPF, and ROA positively affect profit distribution management. Meanwhile, NPF does not affect profit distribution management. ROA is proven to strengthen the effect of CAR and TPF on profit distribution management. While ROA cannot moderate the relationship between NPF and profit distribution management. This study can complement existing theories, especially regarding the relationship between capital adequacy and third-party funds with profit distribution management moderated by ROA. The practical implications of these findings for Islamic bank policies regarding the importance of increasing profitability and reducing problematic financing to maximize profit-sharing management.